2021
DOI: 10.1097/shk.0000000000001811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tissue Perfusion Using the Peripheral Perfusion Index and Lactate Clearance in Shock in Pediatric Patients

Abstract: Background: Pediatric shock has a high mortality rate because many of the early clinical signs are subtle and have poor sensitivity and specificity. Pediatric shock was categorized either: compensated with normal blood pressure, poor skin perfusion (CRT >2 s, mottled, cool peripheries, peripheral cyanosis), weak peripheral pulse, age specific tachycardia, tachypnoea, and oliguria or decompensated with hypotension (SBP < 70 þ (2Â age in years) mm Hg and decreased mental status. The perfusion index is a non-inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Normal values in healthy normal babies of both sexes have been established 26,27 . Furthermore, PPI has also been found to correlate to lactate levels and lactate clearance in pediatric shock patients 28 . Thus, this technique appears potentially useful since it does not need any further electrodes or probes, and the value is possible to get from the already applied pulse oximeter probe.…”
Section: Main Articlementioning
confidence: 93%
See 3 more Smart Citations
“…Normal values in healthy normal babies of both sexes have been established 26,27 . Furthermore, PPI has also been found to correlate to lactate levels and lactate clearance in pediatric shock patients 28 . Thus, this technique appears potentially useful since it does not need any further electrodes or probes, and the value is possible to get from the already applied pulse oximeter probe.…”
Section: Main Articlementioning
confidence: 93%
“…Promising data regarding the use of PPI have recently been reported also in children 26–28 . Normal values in healthy normal babies of both sexes have been established 26,27 .…”
Section: Main Articlementioning
confidence: 97%
See 2 more Smart Citations
“…In this study comparing latest generation ultrasound technology to change in central venous pressure with modification of intrathoracic pressure, the authors identified changes in central venous pressure as the only parameter providing at least modest fluid responsiveness prediction. In contrast to the evaluation of vascular bed predictors just discussed, tissue perfusion parameters and clearance of lactate were assessed in a pediatric patient group by Bazaraa et al (8) from Cairo University. This team studied a Perfusion Index using signal extraction technology based on a pulse oximetry to noninvasively monitor perfusion status.…”
mentioning
confidence: 99%